PP2C1 fine‐tunes melatonin biosynthesis and phytomelatonin receptor PMTR1 binding to melatonin in cassava. Issue 1 (13th May 2022) - Bai, Yujing; Wei, Yunxie; Yin, Hongyan; Hu, Wei; Cheng, Xiao; Guo, Jingru; Dong, Yabin; Zheng, Liyan; Xie, Haoqi; Zeng, Hongqiu; Reiter, Russel J.; Shi, Haitao
Abstract: Melatonin is an important molecule in both animals and plants, regulating circadian rhythms and stress responses. Therefore, the improvement of melatonin accumulation not only strengthens the function of melatonin but also improves stress resistance in crops. Although melatonin biosynthetic enzymes have been identified through reverse genetics previously, an investigation of melatonin level‐related genes through forward genetics in plants has yet to be performed. In this study, a genome‐wide association study using cassava natural population of 298 genetic resources identified melatonin accumulation 1 ( MA1 ), which regulates the natural variation of melatonin levels in cassava. We found that MA1 encodes type 2C protein phosphatase 1 (PP2C1), which serves as a negative regulator of melatonin levels in cassava. MePP2C1 physically interacts with MeRAV1/2 and MeWRKY20 and dephosphorylates them at serine (S) 35 residue, S34 residue, and S176 residue, respectively, thereby hindering their transcriptional activation on downstream melatonin biosynthetic genes. Notably, MePP2C1 interacts with phytomelatonin receptor MePMTR1 and dephosphorylates it at S11 residue, repressing its binding to melatonin. In summary, this study demonstrates that MePP2C1 as MA1 plays dual roles in negatively regulating both melatonin accumulation and signaling, extending the understanding of the molecular mechanism underlying melatonin accumulation and signaling through forward genetics in plants.